Caracterização dos grupos funcionais de espécies arbóreas do cerrado - Borges, Mariana Prado (2016)
The Cerrado is a vegetation complex characterized by climate seasonality that imposes to tree species a water stress during the dry season. Cerrado tree species are frequently classified according to the leaf deciduousness degree as deciduous, evergreen and semideciduous. The association of leaf deciduousness with functional groups is discussed in the literature. Thus, the main aim of this thesis was to test hypotheses about the existence, structure and behavior of functional groups of cerrado tree species and its coincidence with the leaf deciduousness. The characterization of the functional groups aimed to show the relationships of inter-dependencies among the crown characters and how each group responds to environmental stress. For this, we used: (1) metadata of flowering period of 92 species in different localities; (2) metadata of 15 species in the UFSCar cerrado reserve (São Carlos-SP) combined with data collected in field in the same reserve area; and (3) experimental data about climatic alterations in the cerrado, collected in filed, under natural conditions, for the years of 2013 and 2014 in UFSCar reserve. The crown traits distributed in time and space were analyzed at different statistical methods. (ANOVA, chi-square, circular statistic, Kruskal-Wallis, Permanova, scatter plot distribution, and network connectance analyses). According to our results, we concluded: (1) The existence of at least three functional groups of cerrado tree species; (2) The functional groups are in a functional that agree with the leaf phenology; (3) The leaf deciduousness is only one attribute in a list of crown traits (flowering duration, flowering peak, shoot-foliage relationships, crown architecture, shoot inclination, biomass partitioning among crown organs) distinctive of the different groups; (4) The interrelationships among the several crown traits constitutes a syndrome resulting in a distinct plant strategy to overcome the water stress in every functional group; (5) The semideciduous species present exclusive adaptive responses that allow their classification in a separate group of deciduous and evergreen.